Developing Communication Book for Schizophrenia in Aceh: Prospects and Challenges - Maya Khairani; Rizanna Rosemary; Risana Rachmatan; Lely Safrina (Jurnal Ilmu Perilaku, 2021)
he lack of media information about Schizophrenia in Aceh explains caregivers’ limited understanding of mental disorders. Research on patient discharge systems found that communication media about Schizophrenia were still limited, mostly in the form of posters, flyers, or booklets. There was no specific information about the mental illness needed by the family or caregivers after the patient's discharged from the hospital. This study aims to develop and test a communication medium that can support the recovery process of post-discharge patients from the Mental Health Hospital or Rumah Sakit Jiwa (RSJ) in Aceh. This action research was carried out through focus group discussions (FGDs), interviews, and surveys to health practitioners (mental health nurses, psychiatrists, psychologists, community leaders) and family or caregivers of Patients with Schizophrenia (PWS). The study found that messages about Schizophrenia which are developed through a community-based approach are likely to be better accepted than the expert-led information.